Financial Impact and Causes of Chronic Musculoskeletal Disease Cases in Malaysia Based on Social Security Organization of Malaysia Claims Record - Zainal Abidin, Norsheila; Mohd. Rohani, Jafri; Nadia Nordin, Athirah; Md. Zein, Raemy; Satik anak Ayak, Augeny (International Journal of Engineering and Technology, 2018)
This paper analyzed total direct cost that is paid by the Social Security Organization of Malaysia (SOCSO) to the Malaysian workers due to musculoskeletal disease. The objectives of this study are 1) to determine the total direct costs incurred as a result of cases of chronic musculoskeletal injuries that was approved by SOCSO from 2009 to 2014 and 2) to examine the age category imposed for the total average cost of the highest MSDs claims for the four categories setting. The data provided by SOCSO on occupational diseases and adopt the top-down approach which includes of 416 claims reported between 2009 and 2014. The categories recorded are the highest total direct cost for types of industries, types of injury, causes of accident and type of body parts. The age claimant is then identified from total average cost earned from the highest total direct cost of the four categories. Manufacturing industry, strenuous movement, sprain and strain and back are recorded as highest total direct cost with the cost of RM 5,181,282.34, RM 7,088,839.51, RM 8,753,975.13, and RM 5,526,590.69, respectively. The age group of 35 â€“ 44 years is recorded as the highest total average cost of these four parameters. This study will provide the basis for future studies and intervention on MSD related injuries in working environment in Malaysia.Â Â
Keywords: Body part location; Cause of accident; Direct cost; Injury; Musculoskeletal disorders